A long-life micro-surface treatment material and preparation method thereof
By adopting long-life solid waste microsurface treatment materials, combined with the use of modified emulsified asphalt and gelling materials, the problems of short service life, shortage of raw materials and significant noise in the prior art have been solved, and the material's efficiency, durability and environmental protection performance have been improved.
Patent Information
- Application Number
- CN202411072700.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-08-06
AI Technical Summary
The existing micrometer processing materials have short service life, shortage of raw materials and significant noise, which affect their promotion and application.
The long-life solid waste microsurface treatment materials are used, and their compositions include mineral materials, modified emulsified asphalt, gelling materials and specific fillers. Through SMA interrupt grading design and the use of modified emulsified asphalt, the high-temperature stability, low-temperature crack resistance and durability of the material are improved, and noise is reduced through porous structural materials.
It significantly extends the service life of micrometer processing materials, improves its high-temperature stability, low-temperature crack resistance and durability, alleviates the shortage of raw materials, significantly reduces noise, and improves the overall performance of the materials.
Smart Images

Figure BDA0004981319880000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of asphalt pavement maintenance, and in particular to a long-life micro-surface treatment material and a preparation method thereof. Background Art
[0002] In the first few years after the highway was built and put into use, the average quality of the road surface was at a high level. With the continuous effects of traffic load and environment, some asphalt pavement diseases such as rutting, cracks, looseness, etc. will occur. If the road surface is not maintained, the road surface diseases will accelerate, and the disease development will be very serious in the later period of service. Preventive maintenance is a maintenance method developed based on the above maintenance concept, that is, without changing the original road surface structure, the road surface is maintained and repaired in a planned and rapid manner, so as to quickly and effectively alleviate the road surface diseases and improve the road surface function.
[0003] Micro-surfacing is a preventive maintenance technology used in high-grade roads such as highways, urban trunk roads and airport roads. It has the characteristics of waterproofing, anti-skid, restoring surface functions and rapid traffic opening, and has become a commonly used preventive maintenance technology in my country. At present, there are still some problems with micro-surfacing pavements: (1) The service life is short, about 2-3 years, and it is easy to produce grain loss and peeling. The adhesion of the mixture and the adhesion with the original pavement are insufficient; (2) The coarse aggregate uses basalt aggregate with a certain hardness, and the fine aggregate uses pure machine-made sand with sufficient powder, which is gradually facing the problem of raw material shortage; (3) The noise of existing micro-surfacing is significantly higher than that of ordinary asphalt pavement, which causes noise pollution to the surrounding environment, resulting in restrictions on the promotion of micro-surfacing. Therefore, there is an urgent need for a micro-surfacing material to solve the problems of unsatisfactory performance, shortage of raw materials, and high noise of micro-surfacing materials in the existing technology. Summary of the invention
[0004] The purpose of the present application is to provide a long-life micro-surface treatment material and a preparation method thereof, so as to solve the problems of unsatisfactory performance, shortage of raw materials, high noise and the like of the micro-surface treatment material in the prior art.
[0005] The present application provides a long-life solid waste micro-surfacing material, comprising the following components in parts by weight: 1000 parts of mineral material, 100-130 parts of modified emulsified asphalt, 50-100 parts of mixing water, and 30-50 parts of cementitious material.
[0006] Preferably, the mineral material comprises coarse aggregate, fine aggregate, machine-made sand and filler in a mass ratio of (40-60):(15-20):(15-25):(10-15), and SMA discontinuous grading is used for mix design.
[0007] Preferably, the coarse aggregate has a nominal particle size of 5 mm to 10 mm and is steel slag aggregate that has been stably stored for more than half a year after disintegration.
[0008] Preferably, the fine aggregate has a nominal particle size of 3 mm to 5 mm and is steel slag aggregate that has been stably stored for more than half a year after disintegration.
[0009] Preferably, the machine-made sand is obtained by crushing hemp stone, and has a nominal particle size of 0 mm to 3 mm.
[0010] Preferably, the raw materials of the filler include mineral powder, activated carbon, and SBS particles in a mass ratio of 100:(50-100):(75-100), wherein the mineral powder is finely ground limestone stone powder, the activated carbon has a particle size of 0.2mm-0.6mm, a pore size of 2nm-10nm, and is impregnated with a 1:1 mixture of aromatic oil and dichloromethane, and the SBS particles are obtained by SBS crushing, and are linear styrene-butadiene-styrene block copolymers with a number average molecular weight of 90,000-110,000.
[0011] Preferably, the modified emulsified asphalt contains base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion, and water-based epoxy resin in a mass ratio of 100:(4-8):(2-4):(4-6), wherein the base emulsified asphalt is a mixing-type emulsified asphalt with a solid content of 65% made from No. 70 asphalt.
[0012] Preferably, the cementitious material comprises cement, slow-setting slag and sodium silicate in a mass ratio of 100:(100-200):(0.3-0.5).
[0013] The present application provides a method for preparing a long-life micro-surface treatment material, comprising the following preparation steps:
[0014] S1. Mix the base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin, stir evenly to obtain modified emulsified asphalt, and set aside;
[0015] S2, mixing cement, slow-setting slag and sodium silicate evenly to obtain a mixed cementitious material for standby use;
[0016] S3, mixing aromatic oil and dichloromethane in a ratio of 1:1, and soaking activated carbon in the mixture for 5 minutes to fully absorb the aromatic oil and dichloromethane;
[0017] S4, mixing the activated carbon soaked in aromatic oil and dichloromethane with the mineral powder and SBS particles to obtain a filler;
[0018] S5. Design the SMA-10 mix ratio according to the screening results of coarse aggregate, fine aggregate, machine-made sand and filler, and calculate the proportion of each group;
[0019] S6. According to the proportion of each component, the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material are mixed for 30 to 40 seconds until uniform, and then water is added and mixed for 30 to 40 seconds until wet to obtain aggregate;
[0020] S7. Add modified emulsified asphalt to aggregate and stir thoroughly for 30 to 50 seconds at room temperature to prepare the long-life micro-surface treatment material.
[0021] Therefore, the present application adopts the above-mentioned long-life micro-surface treatment material and its preparation method, which has the following characteristics:
[0022] Beneficial effects:
[0023] (1) Styrene-butadiene latex effectively improves the high and low temperature performance of the material, and water-based epoxy resin greatly enhances the bonding performance, thereby improving the high temperature stability, low temperature crack resistance and durability of the micro-surfacing road surface.
[0024] (2) Adopting SMA type gradation design, a skeleton-dense surface layer is formed with coarse aggregate as the skeleton, fine aggregate as the supplement, and machine-made sand as the pore filling. Sufficient mineral powder and asphalt form more mortar, thereby effectively improving the road performance of the micro-surfacing pavement;
[0025] (3) Steel slag aggregate is hard and wear-resistant, providing the material with a high wear-resistant and high-strength skeleton structure, greatly increasing the wear resistance of the material.
[0026] (4) Mineral materials and cementitious materials are almost all recycled solid waste. The large-scale application of steel slag, hemp stone and slag can not only alleviate the problem of resource shortage, lack of road construction materials and rising prices, but also help achieve the goal of energy conservation, emission reduction and cost reduction;
[0027] (5) Adding slow-setting slag powder to the cementitious material can not only avoid the surface shrinkage and cracking caused by the rapid strength formation, but also gradually form strength under the stimulation of alkaline substances such as sodium silicate during the subsequent operation, thereby improving the road performance;
[0028] (6) SBS particles and activated carbon have a certain elasticity and can absorb heavy impact force, thereby buffering the pressure of cars on materials and preventing heavy objects such as cars from damaging the road surface; the steel slag, hemp stone, slag, and activated carbon used are all porous structure materials, which greatly reduces the noise of micro-surface;
[0029] (7) The aromatic oil adsorbed in the activated carbon serves as a source of asphalt binder regeneration agent, which greatly slows down the aging process of asphalt. Dichloromethane dissolves part of the SBS particles and can effectively improve the high-temperature stability of asphalt as a modifier.
[0030] (8) After the mixture is spread, the loose masonite sand is slightly crushed under the rolling of vehicles, and the suspended steel slag aggregates contact each other to form a skeleton structure, and the gaps between the masonite sand and the filler are filled. DETAILED DESCRIPTION
[0031] The present application provides a long-life micro-surface treatment material, comprising the following components in parts by weight: 1000 parts of mineral material, 100-130 parts of modified emulsified asphalt, 50-100 parts of mixing water, and 30-50 parts of cementitious material; the mineral material comprises coarse aggregate, fine aggregate, machine-made sand, and filler, and the mass ratio is (40-60): (15-20): (15-25): (10-15), and the mix ratio design is carried out by adopting SMA discontinuous grading;
[0032] The nominal particle size of the coarse aggregate is 5mm-10mm, which is steel slag aggregate that has been disintegrated and stably stored for more than half a year; the nominal particle size of the fine aggregate is 3mm-5mm, which is steel slag aggregate that has been disintegrated and stably stored for more than half a year; the machine-made sand is obtained by crushing hemp stone, and the nominal particle size is ≤3mm. The raw materials of the filler include mineral powder, activated carbon, and SBS particles, and the mass ratio is 100: (50-100): (75-100), wherein the mineral powder is stone powder ground from limestone, the particle size of the activated carbon is 0.2mm-0.6mm, the pore size is 2nm-10nm, and it is impregnated with a 1:1 mixture of aromatic oil and dichloromethane, and the SBS particles are obtained by conventional SBS crushing, which is a linear structure styrene-butadiene-styrene block copolymer with a number average molecular weight of 90,000-110,000.
[0033] The modified emulsified asphalt contains base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin in a mass ratio of 100:(4-8):(2-4):(4-6), wherein the base emulsified asphalt is a mixing-type emulsified asphalt with a solid content of 65% made of No. 70 asphalt; the cementitious material contains cement, slow-setting slag and sodium silicate in a mass ratio of 100:(100-200):(0.3-0.5).
[0034] The present application provides a method for preparing a long-life micro-surface treatment material, comprising the following preparation steps:
[0035] S1. Mix the base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin, stir evenly to obtain modified emulsified asphalt, and set aside;
[0036] S2, mixing cement, slow-setting slag and sodium silicate evenly to obtain a mixed cementitious material for standby use;
[0037] S3, mixing aromatic oil and dichloromethane in a ratio of 1:1, and soaking activated carbon in the mixture for 5 minutes to fully absorb the aromatic oil and dichloromethane;
[0038] S4, mixing the activated carbon soaked in aromatic oil and dichloromethane, mineral powder and SBS particles uniformly to obtain a filler;
[0039] S5. Design the SMA-10 mix ratio according to the screening results of coarse aggregate, fine aggregate, machine-made sand and filler, and calculate the proportion of each group;
[0040] S6. Mix the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material for 30 to 40 seconds according to the proportion of each component until they are uniform, and then add water and mix for 30 to 40 seconds until they are moist;
[0041] S7. Add modified emulsified asphalt to aggregate and stir thoroughly for 30 to 50 seconds at room temperature to prepare cold-mixed and cold-laid emulsified asphalt mixture.
[0042] Example 1
[0043] The long-life solid waste micro-surfacing material in this embodiment comprises the following components in parts by weight: 1000 parts of mineral material, 115 parts of modified emulsified asphalt, 75 parts of mixing water, and 40 parts of cementitious material.
[0044] The total amount of mineral materials is 100 parts, including the following components in parts by weight: 50 parts of coarse aggregate, 18 parts of fine aggregate, 20 parts of machine-made sand, and 12 parts of filler. The mix ratio design is carried out using SMA discontinuous grading.
[0045] The mineral materials include coarse aggregate, fine aggregate, machine-made sand and filler, with a mass ratio of 50:18:20:12.
[0046] The raw materials of the filler include mineral powder, activated carbon, and SBS particles, with a mass ratio of 100:75:85.
[0047] The modified emulsified asphalt contains base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin in a mass ratio of 100:6:3:5.
[0048] The cementitious material includes cement, slag and sodium silicate in a mass ratio of 100:150:0.4.
[0049] The method for preparing the long-life solid waste micro-surfacing material in this embodiment mainly comprises the following steps:
[0050] S1. Mix the base emulsified asphalt, styrene butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin, stir evenly to obtain modified emulsified asphalt: first, place the base emulsified asphalt in a stirring container; then, add styrene butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin in sequence, use a high-speed stirrer to mix the above materials, stir evenly, and the obtained modified emulsified asphalt is sealed for use.
[0051] S2. Mix cement, slag and sodium silicate evenly to obtain a mixed gelling material: weigh cement, slag and sodium silicate according to a predetermined ratio, then put these materials into a mixing container, and use a stirrer to mix them. During the mixing process, ensure that all ingredients are evenly distributed without particle agglomeration. The obtained gelling material is sealed for later use.
[0052] S3. Mix aromatic oil and dichloromethane in a ratio of 1:1, and soak the activated carbon in the mixture for 5 minutes to fully absorb the aromatic oil and dichloromethane: first, pour equal amounts of aromatic oil and dichloromethane into a container and mix them thoroughly; then, add an appropriate amount of activated carbon into the mixture; put the mixture and activated carbon into a sealed container together, seal it and shake it gently to allow the activated carbon to fully contact with the mixture; after soaking for 5 minutes, the activated carbon will fully absorb the aromatic oil and dichloromethane in the mixture.
[0053] S4. Evenly mix the activated carbon soaked in aromatic oil and dichloromethane with mineral powder and SBS particles to obtain filler: Weigh the activated carbon soaked in aromatic oil and dichloromethane with mineral powder and SBS particles according to a predetermined ratio, put these materials into a stirring container, and mix them using a stirrer. During the mixing process, ensure that all ingredients are evenly distributed without particle agglomeration. After the mixing is completed, transfer the obtained filler to a spare container and seal it for storage.
[0054] S5. SMA-10 mix design is carried out according to the screening results of coarse aggregate, fine aggregate, machine-made sand and filler, and the proportion of each component is calculated: First, the coarse aggregate, fine aggregate, machine-made sand and filler are screened to obtain their respective particle size distribution data. Among them, the nominal particle size of the coarse aggregate is 5mm~10mm, which is the steel slag aggregate that has been disintegrated and stably stored for more than half a year. The nominal particle size of the fine aggregate is 3mm~5mm, which is the steel slag aggregate that has been disintegrated and stably stored for more than half a year. The machine-made sand is obtained by crushing hemp stone, and the nominal particle size is 1.5mm~2.0mm. The diameter is ≤3mm, the mineral powder is the stone powder ground from limestone, the particle size of activated carbon is 0.2mm~0.6mm, the pore size is 2nm~10nm, the SBS particles are obtained by conventional SBS crushing, which is a linear structure of styrene-butadiene-styrene block copolymer with a number average molecular weight of 90,000~110,000. According to the design requirements and particle size distribution data of SMA-10 mixture, the mass proportion of each component is calculated by design software or manually, including 50 parts of coarse aggregate, 18 parts of fine aggregate, 20 parts of machine-made sand and 12 parts of filler.
[0055] S6. According to the proportion of each component, mix the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material for 35 seconds until uniform, and then add water and mix for 35 seconds until wet;
[0056] S7. Add modified emulsified asphalt to aggregate and stir thoroughly for 40 seconds at room temperature to prepare cold-mixed and cold-laid emulsified asphalt mixture.
[0057] Example 2
[0058] The long-life solid waste micro-surfacing material in this embodiment comprises the following components in parts by weight: 1000 parts of mineral material, 100 parts of modified emulsified asphalt, 50 parts of mixing water, and 30 parts of cementitious material.
[0059] The total amount of mineral materials is 100 parts, including the following components in parts by weight: 60 parts of coarse aggregate, 15 parts of fine aggregate, 15 parts of machine-made sand, and 10 parts of filler. The mix ratio design is carried out using SMA discontinuous grading.
[0060] The raw materials of the filler include mineral powder, activated carbon, and SBS particles, with a mass ratio of 100:50:75.
[0061] The modified emulsified asphalt contains base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin in a mass ratio of 100:8:4:6. Among them, the base emulsified asphalt is a mixing emulsified asphalt with a solid content of 65% made of No. 70 asphalt.
[0062] The cementitious material includes cement, slag and sodium silicate in a mass ratio of 100:200:0.5.
[0063] According to the ratio of the above raw materials, the method for preparing the long-life solid waste micro-surface material in this embodiment includes the following steps:
[0064] S1. Mix the base emulsified asphalt, styrene butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin, stir evenly to obtain modified emulsified asphalt: first, place the base emulsified asphalt in a stirring container; then, add styrene butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin in sequence, use a high-speed stirrer to mix the above materials, stir evenly, and the obtained modified emulsified asphalt is sealed for use.
[0065] S2. Mix cement, slag and sodium silicate evenly to obtain a mixed gelling material: weigh cement, slag and sodium silicate according to a predetermined ratio, then put these materials into a mixing container, and use a stirrer to mix them. During the mixing process, ensure that all ingredients are evenly distributed without particle agglomeration. The obtained gelling material is sealed for later use.
[0066] S3. Mix aromatic oil and dichloromethane in a ratio of 1:1, and soak the activated carbon in the mixture for 5 minutes to fully absorb the aromatic oil and dichloromethane: first, pour equal amounts of aromatic oil and dichloromethane into a container and mix them thoroughly; then, add an appropriate amount of activated carbon into the mixture; put the mixture and activated carbon into a sealed container together, seal it and shake it gently to allow the activated carbon to fully contact with the mixture; after soaking for 5 minutes, the activated carbon will fully absorb the aromatic oil and dichloromethane in the mixture.
[0067] S4. Evenly mix the activated carbon soaked in aromatic oil and dichloromethane with mineral powder and SBS particles to obtain filler: Weigh the activated carbon soaked in aromatic oil and dichloromethane with mineral powder and SBS particles according to a predetermined ratio, put these materials into a stirring container, and mix them using a stirrer. During the mixing process, ensure that all ingredients are evenly distributed without particle agglomeration. After the mixing is completed, transfer the obtained filler to a spare container and seal it for storage.
[0068] S5. SMA-10 mix design is carried out according to the screening results of coarse aggregate, fine aggregate, machine-made sand and filler, and the proportion of each component is calculated: First, the coarse aggregate, fine aggregate, machine-made sand and filler are screened to obtain their respective particle size distribution data. Among them, the nominal particle size of the coarse aggregate is 5mm~10mm, which is the steel slag aggregate that has been disintegrated and stably stored for more than half a year. The nominal particle size of the fine aggregate is 3mm~5mm, which is the steel slag aggregate that has been disintegrated and stably stored for more than half a year. The machine-made sand is obtained by crushing hemp stone, and the nominal particle size is 1.5mm~2.0mm. The diameter is ≤3mm, the mineral powder is the stone powder ground from limestone, the particle size of activated carbon is 0.2mm~0.6mm, the pore size is 2nm~10nm, the SBS particles are obtained by conventional SBS crushing, which is a linear structure of styrene-butadiene-styrene block copolymer with a number average molecular weight of 90,000~110,000. According to the design requirements and particle size distribution data of SMA-10 mixture, the mass proportion of each component is calculated by design software or manually, including 60 parts of coarse aggregate, 15 parts of fine aggregate, 15 parts of machine-made sand and 10 parts of filler.
[0069] S6. According to the proportion of each component, mix the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material for 35 seconds until uniform, and then add water and mix for 35 seconds until moist: according to the obtained proportion, put the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material into a mixing container; use a stirrer to mix the above materials for 35 seconds to ensure uniform mixing; then, add an appropriate amount of water and continue mixing for 35 seconds to make the mixture reach a moist state to obtain the mixed aggregate.
[0070] S7. Add modified emulsified asphalt to the aggregate and stir it thoroughly for 40 seconds at room temperature to prepare a cold-mixed and cold-laid emulsified asphalt mixture: Pour the modified emulsified asphalt evenly into the mixed aggregate obtained in step S6, and use a stirrer to mix the modified emulsified asphalt and the aggregate for 40 seconds to ensure that the mixture is uniform. During the mixing process, control the stirring speed and time to avoid excessive stirring that may cause the emulsified asphalt to demulsify. After the mixing is completed, a cold-mixed and cold-laid emulsified asphalt mixture can be obtained.
[0071] Example 3
[0072] The long-life solid waste micro-surfacing material in this embodiment comprises the following components in parts by weight: 1000 parts of mineral material, 130 parts of modified emulsified asphalt, 100 parts of mixing water, and 50 parts of cementitious material.
[0073] The total amount of mineral materials is 100 parts, including the following components in parts by weight: 40 parts of coarse aggregate, 20 parts of fine aggregate, 25 parts of machine-made sand, and 15 parts of filler. The mix ratio design is carried out using SMA discontinuous grading.
[0074] The raw materials of the filler include mineral powder, activated carbon, and SBS particles, with a mass ratio of 100:100:100.
[0075] The modified emulsified asphalt contains base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin in a mass ratio of 100:4:2:4. Among them, the base emulsified asphalt is a mixing emulsified asphalt with a solid content of 65% made of No. 70 asphalt.
[0076] The cementitious material includes cement, slag and sodium silicate in a mass ratio of 100:100:0.3.
[0077] According to the ratio of the above raw materials, the method for preparing the long-life solid waste micro-surface material in this embodiment includes the following steps:
[0078] S1. Mix the base emulsified asphalt, styrene butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin, stir evenly to obtain modified emulsified asphalt: first, place the base emulsified asphalt in a stirring container; then, add styrene butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin in sequence, use a high-speed stirrer to mix the above materials, stir evenly, and the obtained modified emulsified asphalt is sealed for use.
[0079] S2. Mix cement, slag and sodium silicate evenly to obtain a mixed gelling material: weigh cement, slag and sodium silicate according to a predetermined ratio, then put these materials into a mixing container, and use a stirrer to mix them. During the mixing process, ensure that all ingredients are evenly distributed without particle agglomeration. The obtained gelling material is sealed for later use.
[0080] S3. Mix aromatic oil and dichloromethane in a ratio of 1:1, and soak the activated carbon in the mixture for 5 minutes to fully absorb the aromatic oil and dichloromethane: first, pour equal amounts of aromatic oil and dichloromethane into a container and mix them thoroughly; then, add an appropriate amount of activated carbon into the mixture; put the mixture and activated carbon into a sealed container together, seal it and shake it gently to allow the activated carbon to fully contact with the mixture; after soaking for 5 minutes, the activated carbon will fully absorb the aromatic oil and dichloromethane in the mixture.
[0081] S4. Evenly mix the activated carbon soaked in aromatic oil and dichloromethane with mineral powder and SBS particles to obtain filler: Weigh the activated carbon soaked in aromatic oil and dichloromethane with mineral powder and SBS particles according to a predetermined ratio, put these materials into a stirring container, and mix them using a stirrer. During the mixing process, ensure that all ingredients are evenly distributed without particle agglomeration. After the mixing is completed, transfer the obtained filler to a spare container and seal it for storage.
[0082] S5. SMA-10 mix design is carried out according to the screening results of coarse aggregate, fine aggregate, machine-made sand and filler, and the proportion of each component is calculated: First, the coarse aggregate, fine aggregate, machine-made sand and filler are screened to obtain their respective particle size distribution data. Among them, the nominal particle size of the coarse aggregate is 5mm~10mm, which is the steel slag aggregate that has been disintegrated and stably stored for more than half a year. The nominal particle size of the fine aggregate is 3mm~5mm, which is the steel slag aggregate that has been disintegrated and stably stored for more than half a year. The machine-made sand is obtained by crushing hemp stone, and the nominal particle size is 1.5mm~2.0mm. The diameter is ≤3mm, the mineral powder is finely ground limestone powder, the particle size of activated carbon is 0.2mm~0.6mm, the pore size is 2nm~10nm, and the SBS particles are obtained by conventional SBS crushing. It is a linear structure of styrene-butadiene-styrene block copolymer with a number average molecular weight of 90,000~110,000. According to the design requirements and particle size distribution data of SMA-10 mixture, the mass proportion of each component is calculated by design software or manually, including 40 parts of coarse aggregate, 20 parts of fine aggregate, 25 parts of machine-made sand and 15 parts of filler.
[0083] S6. According to the proportion of each component, mix the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material for 35 seconds until uniform, and then add water and mix for 35 seconds until moist: according to the obtained proportion, put the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material into a mixing container; use a stirrer to mix the above materials for 35 seconds to ensure uniform mixing; then, add an appropriate amount of water and continue mixing for 35 seconds to make the mixture reach a moist state to obtain the mixed aggregate.
[0084] S7. Add modified emulsified asphalt to the aggregate and stir it thoroughly for 40 seconds at room temperature to prepare a cold-mixed and cold-laid emulsified asphalt mixture: Pour the modified emulsified asphalt evenly into the mixed aggregate obtained in step S6, and use a stirrer to mix the modified emulsified asphalt and the aggregate for 40 seconds to ensure that the mixture is uniform. During the mixing process, control the stirring speed and time to avoid excessive stirring that may cause the emulsified asphalt to demulsify. After the mixing is completed, a cold-mixed and cold-laid emulsified asphalt mixture can be obtained.
[0085] Comparative Example 1
[0086] The only difference between this embodiment and Embodiment 1 is the mass percentage of the mineral material. Specifically, the mineral material is calculated according to the mass percentage. The total amount of the mineral material is 100 parts, which includes the following components in parts by weight: 25 parts of coarse aggregate, 12 parts of fine aggregate, 57 parts of machine-made sand, and 6 parts of filler. AC continuous grading is used for mix design.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 1 is that the filler in this comparative example contains only mineral powder and no activated carbon or SBS particles.
[0089] Comparative Example 3
[0090] The only difference between this comparative example and Example 1 is that the coarse and fine aggregates in this comparative example are both basalt.
[0091] Comparative Example 4
[0092] The only difference between this comparative example and Example 1 is that the binder in this comparative example is ordinary modified emulsified asphalt.
[0093] The performance test results of the micro-surface treated materials of Example 1 and Comparative Examples 1 to 4 are shown in Table 1.
[0094] Table 1 Performance test results of micro-surface treated materials
[0095]
[0096] It can be seen from Table 1 that the long-life solid waste micro-surfacing material and the preparation method thereof of the present invention can meet the requirements of the test procedures for asphalt and asphalt mixtures of highway engineering in my country.
[0097] Therefore, the present application provides a long-life micro-surface treatment material and a preparation method thereof, which solve the problems of unsatisfactory performance, shortage of raw materials, high noise, etc. of micro-surface treatment materials in the prior art.
[0098] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0099] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A long-life micro-surface treatment material, characterized in that: The invention comprises the following components in parts by weight: 1000 parts of mineral material, 100-130 parts of modified emulsified asphalt, 50-100 parts of mixing water, and 30-50 parts of cementitious material; The mineral material comprises coarse aggregate, fine aggregate, machine-made sand and filler, with a mass ratio of (40-60): (15-20): (15-25): (10-15), and the mix ratio is designed by SMA discontinuous grading; The raw materials of the filler include mineral powder, activated carbon, and SBS particles, with a mass ratio of 100: (50-100): (75-100), wherein the mineral powder is finely ground limestone; The activated carbon has a particle size of 0.2 mm to 0.6 mm and a pore size of 2 nm to 10 nm, and is impregnated with a mixture of aromatic oil and dichloromethane in a ratio of 1:1; The SBS particles are obtained by SBS crushing, and are styrene-butadiene-styrene block copolymers of a linear structure, and the number average molecular weight thereof is 90,000 to 110,000.
2. A long-life micro-surface treatment material according to claim 1, characterized in that: The coarse aggregate has a nominal particle size of 5 mm to 10 mm and is steel slag aggregate that has been disintegrated and stably stored for more than half a year.
3. A long-life micro-surface treated material according to claim 1, characterized in that: The fine aggregate has a nominal particle size of 3 mm to 5 mm and is steel slag aggregate that has been disintegrated and stably stored for more than half a year.
4. A long-life micro-surface treated material according to claim 1, characterized in that: The machine-made sand is obtained by crushing macadamia stone, and has a nominal particle size of 0 mm to 3 mm.
5. The long-life micro-surface treated material according to claim 3, characterized in that: The modified emulsified asphalt contains base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion, and water-based epoxy resin in a mass ratio of 100:(4-8):(2-4):(4-6), wherein the base emulsified asphalt is a mixing-type emulsified asphalt made of No. 70 asphalt with a solid content of 65%.
6. A long-life micro-surface treated material according to claim 3, characterized in that: The cementitious material comprises cement, slow-setting slag and sodium silicate in a mass ratio of 100:(100-200):(0.3-0.5).
7. The method for preparing a long-life micro-surface treatment material according to claim 3, characterized in that: The method comprises the following preparation steps: S1. Mix the base emulsified asphalt, styrene-butadiene latex, oxidized polyethylene wax emulsion and water-based epoxy resin, stir evenly to obtain modified emulsified asphalt, and set aside; S2, mixing cement, slow-setting slag and sodium silicate evenly to obtain a mixed cementitious material for standby use; S3, mixing aromatic oil and dichloromethane in a ratio of 1:1, and soaking activated carbon in the mixture for 5 minutes to fully absorb the aromatic oil and dichloromethane; S4, mixing the activated carbon soaked in aromatic oil and dichloromethane with the mineral powder and SBS particles to obtain a filler; S5. Design the SMA-10 mix ratio according to the screening results of coarse aggregate, fine aggregate, machine-made sand and filler, and calculate the proportion of each group; S6. According to the proportion of each component, the coarse aggregate, fine aggregate, machine-made sand, filler and cementitious material are mixed for 30 to 40 seconds until uniform, and then water is added and mixed for 30 to 40 seconds until wet to obtain aggregate; S7. Add modified emulsified asphalt to aggregate and stir thoroughly for 30 to 50 seconds at room temperature to prepare the long-life micro-surface treatment material.